THE USE OF ENGLISH TO PROMOTE MOUNTAINEERING ACTIVITIES VIA “BAMBANGAN BASECAMP” ON INSTAGRAM - Mawarti, Tri; Purwandari, Gigih Ariastuti; Hadiningrum, Indriyati (Jurnal Vokasia, 2022)
Bambangan Basecamp is a tourism sector engaged in nature tourism and under the auspices of Perum Perhutani KPH East Banyumas. The purposes are to carry out promotion activities for Bambangan Basecamp through Instagram, to do direct practice in making flyer designs and captions uploaded on Instagram using English. The writer conducted observations, interviews, and documentation to collect data. When conducting interviews, the writer found that not only domestic tourists but also foreign tourists visit Bambangan Basecamp. Therefore, the writer carries out promotions by using English to bridge the language differences in the language. The promotion is done activities carried out by the writer are by making flyer designs and captions in English. The stages include platform determination, content design, design consultation, and implementation of activities. The results have been uploaded to the @slametviabambangan Instagram feed. The obstacles that the writer encountered are the information in Bambangan Basecamp is not being equipped with English and limitations in using English in promotion activities. To overcome these obstacles, the writer looks for related information references, conducts consultations with supervisors, and uses several dictionary assistance online and offline.